Begonia triquetra (sect. Platycentrum, Begoniaceae), a new subpeltate-leaved species from limestone hills in Son La province, Northwestern Vietnam - Anh, Tran Thi Phuong; Thanh, Nguyen Thi; Quang, Bui Hong; Binh, Tran Duc; Thanh, Trinh Xuan; Le, Anh Tuan; Nguyen, Khang Sinh; Lin, Che Wei (Phytotaxa, 2024)
Begonia triquetra, a new species endemic to the limestone karst regions of Son La province in Northwestern Vietnam, is described and illustrated here. This new species resembles B. xenos in its suberect habit, subpeltate lamina, 4-tepaled staminate flowers, and 2-locular ovary. However, B. triquetra differs significantly from B. xenos in having triangular (vs. terete) cross section of petiole, entire (vs. slightly crenulate) staminate tepals, and zygomorphic (vs. actinomorphic) androecium with 18–24 (vs. 52–85) stamens. Notes on ecology and conservation status are preliminarily provided to the new species.